Quantifying the sources and health risks of groundwater nitrate via dual NO isotopes and Monte Carlo simulations in a developed planting-breeding area - Jianwei Liu; Shuo Qiao; Shilong Zhao; Hui Chen; Yong Wu; Donghao Li; Ping Liu; Ling Li (Ecotoxicology and Environmental Safety)
Nitrate (NO3−) pollution in groundwater is a worldwide environmental issue, particularly in developed planting-breeding areas where there is a substantial presence of nitrogen-related sources. Here, we explored the key sources and potential health risks of NO3− in a typical planting-breeding area in the North China Plain based on dual stable isotopes and Monte Carlo simulations. The analysis results revealed that the NO3− concentration ranged from 0.02 to 44.6 mg/L, with a mean value of 7.54 mg/L, along with a significant spatial variability. Analysis by combining stable isotopes (δ15N-NO3− and δ18O-NO3−) with the Bayesian isotope mixing model (MixSIAR) revealed that soil N (60.3 %) and manure and sewage (35.9 %) contributed the most NO3− in groundwater, followed by chemical N fertilizer (2.9 %) and atmospheric N deposition (0.8 %). However, the contribution of N fertilizer may be underestimated because it has undergone a long-term applied history and have progressively accumulated in the soil, and then promoted the entry of groundwater under frequent rainfall and irrigation practices. From the probabilistic health risk assessment, a relatively low probability of exceeding the threshold (HI=1) was observed (0.2 % for adults and 2.59 % for children); nevertheless, children still face some nonnegligible risk, particularly for the oral ingestion of drinking water at high-pollution sites. Therefore, we highlight the importance of effective management of manure and sewage from breeding plants and reduction of chemical N fertilizer usage are suggested in developed agricultural areas.